A circular design process for material selection in site design - Chen, Si (Kansas State University, 2021)
2020 is the first year that all mass embedded in human-made products has surpassed the amount of biomass on our planet (Oxman 2020). Even so, the demands for raw materials are still increasing, when almost one fourth of the materials extracted worldwide end up as waste (OECD 2015). While there is a call for sustainably reusing site design materials, it is difficult for landscape architects to respond to the call without having a material selection process that optimizes reusing and recycling materials. However, this need for a material selection process for landscape architects can be realized through “circular design”. Circular design has successfully been used in architecture and product design to help reduce project costs, emissions, waste, and pollution. Yet in landscape architecture, the use of circular design is not wide spread. To answer the question “how can a circular design process guide material selection in site design, and what are the tradeoffs when it is compared to existing linear and sustainable processes,” this research proposed a circular design process for material selection in site design and applied it to the plaza design of MLK Jr. Square Park in Kansas City, Missouri. The proposed circular design process was generated from a comparative study of the existing best practices of circular design in other disciplines and from existing guidelines for sustainable materials selection. By applying the linear, sustainable, and circular design processes, three material palettes and plaza designs were created to illustrate the tradeoffs between each material selection process. The results reveal both the benefits and shortcomings of the proposed circular design process for material selection in site design. The proposed circular design process requires more time and effort during project management, design, and construction phases than the linear and sustainable processes do. While the sustainable process addresses a wide range of environmental impacts such as reducing waste, stormwater runoff, urban heat island effect, and volatile organic compounds, the circular design process prioritizes waste reduction and resource conservation. Although the application of the circular design process for material selection in site design is challenging, due to the uncertainty of available recycled materials and the limited tolerance of irregular design elements, it performs best in reducing waste, energy, and resource consumption. And because circular design prioritizes the use of recycled, reused, and repurposed materials, it also has a strong potential to reduce environmental impacts associated with material extraction, processing, manufacturing, and disposal.
Keywords: Site design; Circular design; Material recycling; Design for disassembly; Material selection; Sustainable material